2007
DOI: 10.2189/asqu.52.3.443
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Brokerage, Generative Creativity, and Creative Success

Abstract: Analyzing data on utility patents from 1975 to 2002 in the careers of 35,400 collaborative inventors, this study examines the influence of brokered versus cohesive collaborative social structures on an individual's creativity. We test the hypothesis that brokerage—direct ties to collaborators who themselves do not have direct ties to each other—leads to greater collaborative creativity. We then test interaction hypotheses on the marginal benefits of cohesion, when collaborators have independent ties between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
747
1
11

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 971 publications
(806 citation statements)
references
References 79 publications
23
747
1
11
Order By: Relevance
“…In particular, they allow for a better appreciation of the collective dimension of knowledge dynamics. Knowledge is indeed viewed as the outcome of a combinatorial activity in which intentional and unintentional exchange among innovating agents provides the access to external knowledge inputs (Fleming and et al, 2007). The network dynamics of innovating agents provide the basis for the emergence of new technological knowledge, which is in turn represented as an organic structure, characterized by elementary units and by the connections amongst them.…”
Section: The Implementation Of Knowledge Indicatorsmentioning
confidence: 99%
“…In particular, they allow for a better appreciation of the collective dimension of knowledge dynamics. Knowledge is indeed viewed as the outcome of a combinatorial activity in which intentional and unintentional exchange among innovating agents provides the access to external knowledge inputs (Fleming and et al, 2007). The network dynamics of innovating agents provide the basis for the emergence of new technological knowledge, which is in turn represented as an organic structure, characterized by elementary units and by the connections amongst them.…”
Section: The Implementation Of Knowledge Indicatorsmentioning
confidence: 99%
“…For example, Granovetter (1973) maintains that weak tie sources are often more important in spreading information or resources because they tend to serve as a bridge between otherwise disconnected social groups. Following that line of thought, Coradi, Heinzen, and Boutellier (2015) points out that as weak tie sources have a low degree of connectivity, they do not provide the deep social support of dense networks; thus such sources provide more opportunities to secure new information and diverse perspectives that can facilitate ideas (Fleming, Mingo, & Chen, 2007). Previous research has also found that weak tie sources transfer and secure codified knowledge efficiently and easily (Hansen, 1999).…”
Section: Antecedents Of Breadth Of Absorptive Capacitymentioning
confidence: 97%
“…Knowledge moderation. As noted previously, the positive correlation between collaboration and higher research quality in cross-sectional data suffers from "reverse causality and survivor bias" (Fleming, Mingo, & Chen, 2007). The causal effect requires that the left-side variable, research quality indicator(s) (JIF and CITATIONS), is the result of the right-side variable, international collaboration.…”
Section: Variablesmentioning
confidence: 98%
“…This situation should also be taken into consideration for such an interdisciplinary field as nanotechnology. This research controls for this factor by adopting the Fraunhofer ISI classification method, which categorizes nanotechnology research into 24 research fields based on subject category codes (Frietsch et al, 2007).…”
Section: Scope Of Research Collaborationmentioning
confidence: 99%
See 1 more Smart Citation